Detecting and discriminating novel objects: The impact of perirhinal cortex disconnection on hippocampal activity patterns. Issue 11 (22nd July 2016) - Kinnavane, Lisa; Amin, Eman; Olarte‐Sánchez, Cristian M.; Aggleton, John P.
ABSTRACT: Perirhinal cortex provides object‐based information and novelty/familiarity information for the hippocampus. The necessity of these inputs was tested by comparing hippocampal c‐ fos expression in rats with or without perirhinal lesions. These rats either discriminated novel from familiar objects (Novel‐Familiar) or explored pairs of novel objects (Novel‐Novel). Despite impairing Novel‐Familiar discriminations, the perirhinal lesions did not affect novelty detection, as measured by overall object exploration levels (Novel‐Novel condition). The perirhinal lesions also largely spared a characteristic network of linked c‐ fos expression associated with novel stimuli (entorhinal cortex→CA3→distal CA1→proximal subiculum). The findings show: I) that perirhinal lesions preserve behavioral sensitivity to novelty, whilst still impairing the spontaneous ability to discriminate novel from familiar objects, II) that the distinctive patterns of hippocampal c‐ fos activity promoted by novel stimuli do not require perirhinal inputs, III) that entorhinal Fos counts (layers II and III) increase for novelty discriminations, IV) that hippocampal c‐ fos networks reflect proximal‐distal connectivity differences, and V) that discriminating novelty creates different pathway interactions from merely detecting novelty, pointing to top‐down effects that help guide object selection. © 2016 The Authors Hippocampus Published by Wiley Periodicals, Inc.